ProManageTI Integrated System for Managing Internships, Proposals, and Final Projects in Informatics Engineering Students - Muhammad Faldza Fadhillah; Bias Yulisa Geni (Journal of Information Systems and Technology Research, 2026)
This study presents the design and development of ProManageTI, a web-based integrated system for managing and monitoring Internship (KP), Final Project Proposals (Proposal TA), and Final Projects (TA) in the Informatics Engineering Study Program at Universitas Dian Nusantara. The research problem addressed is the inefficiency and lack of integration in the manual process using Google Workspace tools, which led to fragmented data, delays in academic workflows, and limited real-time progress tracking. The objective of this study is to provide a structured digital platform that enhances effectiveness, transparency, and accountability in academic process management. The system was developed using the Agile methodology with the Scrum framework, implemented with PHP, MySQL, and Bootstrap, and designed through Unified Modeling Language (UML) diagrams. It integrates features such as title submission, supervision monitoring, scheduling, document verification, notifications, and centralized document storage. Functional testing applied the Black Box method with Equivalence Partition and Boundary Value Analysis techniques, confirming that all features met requirements. The findings indicate that ProManageTI improves operational efficiency, data accuracy, and coordination among students, supervisors, and program administrators. The contribution and novelty of this research are the provision of a scalable and adaptable model for integrated academic management, enabling structured, accountable, and responsive academic services that can be replicated in broader higher education contexts.